Tingkat Kepuasan Peserta Didik pada Pembelajaran Matematika di Masa Pandemi Covid-19 - Muhammad Safak (LPMP Provinsi DKI Jakarta, 2021)
During the Covid-19 pandemic, there was a change in teaching and learning activities for students and teachers from face-to-face learning to distance learning (PJJ) activities. Students satisfaction in the implementation of PJJ is determined by the design of teaching materials and teacher services. The purpose of the study was to analyze the level of students satisfaction in learning mathematics during the pandemic. The research was conducted at SMP Negeri 1 Lumajang using a descriptive method with survey techniques. Collecting data using a questionnaire with googleform. The results showed that the level of student satisfaction with learning during the pandemic was 86.50% (very satisfied). The student satisfaction includes the teacher's ability to compose: contextual material (79.19%), accuracy of teaching materials (89.17%), suitability of material (88.33%), motivating (90.83%), punctuality (85% ), encouraging (91.67%), evaluating (87%), preparing programs (85.83%), communicating (81.67%), teacher’s concern (89.17%), responding (88.33%), involvement (87.50%), good teaching aids (82.50%), material access (85.00%), task access (84.17%)